RELATIONSHIP BETWEEN PEER CONFORMITY AND STUDENTS' POLITE ATTITUDES TOWARDS TEACHERS OF SMP AHMAD DAHLAN JAMBI CITY - Rahmatillah, Wirda; Sutja, Akmal; Yusra, Affan (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
This research is motivated by problems related to student courtesy towards teachers, student manners are influenced by various factors, one of which is external factors due to the presence of students, one of which is peer conformity. The purpose of this study was to reveal the quality of students' politeness towards teachers and peer conformity and to reveal the relationship between peer conformity and students' polite attitudes towards teachers.In this study what is meant by peer conformity is seen from obedience, agreement and cohesiveness between peers, while students' courtesy towards teachers is limited to how students talk to teachers and treat teachers,This study used a quantitative approach with the correlation research method. As for sampling using the Total Sampling technique, the sample used in this study was 70 class VII students for the 2022/2023 academic year, SMP Ahmad Dahlan, Jambi City. This study uses a Likert scale,The results showed that peer conformity had a percentage of 73%, while the politeness of students towards teachers was 53%. hypothesis test m, showing the correlation analysis of the two variables is r = 0.525. there is a significant positive relationship between peer conformity and the polite attitude of students towards Jambi City teachers, and it is included in the correlation 0.41-0.70, which means that the correlation is moderate: adequate relationship. Based on the counseling teacher can make a program about counseling services in order to educate students regarding peer conformity and politeness